Cobalt-Catalyzed Alkylation of Drug-Like Molecules and Pharmaceuticals Using Heterocyclic Phosphonium Salts - Zhang, Xuan; McNally, Andrew (ACS catalysis, 2019)
Alkylated pyridines are common in pharmaceuticals, and metal catalysis is frequently used to prepare this motif via Csp2–Csp3 coupling processes. We present a cobalt-catalyzed coupling reaction between pyridine phosphonium salts and alkylzinc reagents that can be applied to complex drug-like fragments and for late-stage functionalization of pharmaceuticals. The reaction generally proceeds at room temperature, and 4-position pyridine C–H bonds are the precursors in this strategy. Given the challenges in selectively installing (pseudo)halides in complex pyridines, this two-step process enables sets of molecules to be alkylated that would be challenging using traditional cross-coupling methods.